The effect of ticagrelor on microarterial thrombosis in an experimental model - Okur, Mehmet Ihsan; Cetinbas, Ahmet; Altun, Serdar; Oztan, Mehmet; Altun, Aysun Yildiz; Ozercan, Ibrahim (Medical Journal Sweden Ab, 2021)
Thromboses that form in the pedicle after free flap and/or replantation may result in the loss of the flap and/or limb. Ticagrelor is an adenosine diphosphate (ADP) receptor antagonist antithrombotic that can inhibit ADP-dependent platelet activation and aggregation. It is clinically used in acute coronary syndrome and unstable angina. However, its effect on microarterial anastomoses has not been investigated in the literature. An experimental thrombosis model was developed in both femoral arteries of a total of 40 rats. Twenty rats were randomly selected as the drug-free control group, and 20 rats were randomly selected as the ticagrelor group. The rats in the ticagrelor group were administered a 20 mg/kg loading dose orally by gavage 24 h before the experiment, and a maintenance dose of 2x10 mg/kg ticagrelor for 14 days after surgery. After the experiment, the femoral artery was evaluated for macroscopic and microscopic thrombosis, inflammation, edema, and endothelialization. Macroscopically and microscopically, thrombosis was observed at rates of 73.3% and 33.3% in the control group and the ticagrelor group, respectively. Inflammation in the vessel wall was found as 56.7% in the control group and 16.7% in the ticagrelor group. Edema in the vessel wall was found in 63.3% of the control group and 20% of the ticagrelor group. A statistical difference was found between the two groups in terms of thrombosis, inflammation, and edema. Both groups had similar characteristics in terms of endothelialization. Ticagrelor has a reducing effect on thrombosis in the microarterial tuck model.
Keywords: Microsurgery; thrombus; ticagrelor; rat tuck model